The crimson kimono - Sukman, Harry 1912-1984 (Powerhouse Films, 2021)
"Two detectives seek a stripper's killer in the Japanese quarter of Los Angeles, but a love triangle threatens their friendship." [imdb.com]
Original: USA 1959
Indicator Blu-Ray edition special features: High Definition remaster ; original mono audio ; The Culture of ‘The Crimson Kimono’ (2009, 10 mins): analysis by filmmaker Curtis Hanson ; Switch-Hitting Between Three Triangles (2018, 15 mins): audiovisual essay by Cristina Álvarez López ; Sam Fuller Storyteller (2009, 25 mins): insightful documentary with contributions from Martin Scorsese and Wim Wenders, as well as Fuller’s wife, Christa, and daughter, Samantha ; Sam Fuller on Henry Chapier’s Couch (1989, 22 mins): archival interview from French TV in which Fuller answers questions about his life ; ‘The Typewriter, the Rifle & the Movie Camera’ Rushes Tapes 01-06 (1996, 194 mins): unedited interview footage of Sam Fuller in conversation with actor Tim Robbins, recorded for Adam Simon’s classic documentary ; original theatrical trailers ; image gallery: publicity photography and promotional material ; new and improved English subtitles for the deaf and hard-of-hearing
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc